Penerapan Model Pembelajaran Connecting Organizing Reflecting Extending untuk Meningkatkan Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMP Negeri 19 Padang - BUNGA OKTARI ALDI (Departemen Matematika, 2019)
Understanding the concept is a basic ability that must be possessed by every student. But in reality learning is still centered on the teacher, the teacher actively provides information to students, while students are still passive in learning. So that, it results in understanding of concepts and learning activities of low students. One of the efforts made to improve students' understanding of concepts is to apply the Connecting Organizing Reflecting Extending (CORE) learning model. The purpose of this study is to describe whether understanding mathematical concepts of students who learn by learning CORE is better than understanding mathematical concepts of students who learn by direct learning.Based on the results of the data analysis, it was concluded that understanding mathematical concepts of students who learn using the CORE learning model is better than understanding concepts of students who learn by direct learning. Likewise the learning activities of students also increased after the CORE learning model was applied. Keyword – Understanding of mathematical concepts, the Connecting Organizing Reflecting Extending